Atypical Antipsychotics as Augmentation Therapy in Anorexia Nervosa - Marzola, Enrica (PLoS One, 2015)
Anorexia nervosa (AN) is a life-threatening and difficult to treat mental illness with the highest mortality rates of any psychiatric disorder. We aimed to garner preliminary data on the real-world use of olanzapine and aripiprazole as augmentation agents of Selective Serotonin Reuptake Inhibitors (SSRIs) in adult inpatients affected by AN. We retrospectively evaluated the clinical charts of patients who were hospitalized between 2012 and 2014. Patients were evaluated upon admission and discharge. We investigated eating symptomatology, and both general and eating psychopathology using: Hamilton Rating Scale for Anxiety, Hamilton Rating Scale for Depression, and Yale-Brown-Cornell Eating Disorders Scale. The charts of 75 patients were included in this study. The sample resulted equally distributed among those receiving SSRIs and either aripiprazole or olanzapine in addition to SSRIs. Notwithstanding a few baseline clinical differences, upon discharge all groups were significantly improved on all measures. Interestingly, aripiprazole showed the greatest effectiveness in reducing eating-related preoccupations and rituals with a large effect size. The body of evidence on medication management in AN is in dismal condition. Augmentation therapy is a well-established approach to a variety of mental disorders and it is often used in every-day clinical practice with patients affected by AN as well. Nevertheless, to date very little data is available on this topic. Results from our sample yielded promising results on the effectiveness of aripiprazole augmentation in reducing eating-related obsessions and compulsions. Randomized controlled trials are warranted to confirm these encouraging findings.